Pemanfaatan Media Canva dalam Presentasi Belajar Mahasiswa STAI Ibnu Rusyd Kotabumi - Syukron Ar Rasyid IGB; Ariyanto Ariyanto; Indah Kumala Putri; Nurul Andini; Dessy Kurnia Mulyani (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Technological progress is something that cannot be avoided in this life, where the world has shifted from the era of industrialization to the era of digital technology. The Canva application is a web-based platform that can be used to create various interesting designs. There are many features that can be used in Canva, including graphics, posters, presentations, flyers, brochures, and so on. The approach used in this research is descriptive qualitative. Qualitative research is a research method used to examine the condition of a natural object. The researcher's aim is to determine the use of Canva media in STAI Ibnu Rushd Kotabumi learning presentations. The results and discussion of this researcher are that the Canva application is a web-based platform that can be used to create various interesting designs. The material that will be made into a learning video uses Canva design.